From Shock to Adaptation: Evaluating the Mechanisms of Trade Friction on Firms’ Total Factor Productivity Through the Lens of Digital Transformation - Xiyin Zhang; Xindong Zhang (Systems)
Against the backdrop of frequent global trade conflicts and accelerated competition in the digital economy, we investigated how trade friction shocks affect firms’ total factor productivity (TFP), with a focus on the role of digital transformation. We employed a statistical analysis method based on the multi-period difference-in-differences model with anti-dumping and countervailing measures as quasi-natural experiments to analyze firm-level panel data for Chinese exporters from 2003 to 2016. The results indicate that trade frictions compel export firms to enhance their TFP, while digital transformation further promotes this growth. This main conclusion still holds after a series of tests such as parallel trend checks, placebo tests, and variations in primary variables. The mechanism analysis shows that, in response to trade friction shocks, firms aiming to boost productivity have strategically reallocated internal resources by increasing exports of alternative products and expanding into overseas markets rather than solely relying on innovation. Additionally, digital transformation mitigates the negative effects of trade friction on firm innovation and facilitates faster internal resource reallocation during such challenges. The heterogeneity analysis reveals that digital transformation proves more beneficial for firms that are multi-product, non-state-owned, engaged in general trade, and operating in highly competitive industries. This paper contributes to the understanding of trade friction and productivity at the micro level, offering valuable insights into digital transformation strategies for firms navigating these challenges.